Long-term warming and nitrogen fertilization affect C-, N- and P-acquiring hydrolase and oxidase activities in winter wheat monocropping soil - Zhang, Chuang; Dong, Wenxu; Manevski, Kiril; Hu, Wenpei; Timilsina, Arbindra; Chen, Xiaoru; Zhang, Xinyuan; Hu, Chunsheng (Scientific reports, 2021)
The enzymatic activities and ratios are critical indicators for organic matter decomposition and provide potentially positive feedback to carbon (C) loss under global warming. For agricultural soils under climate change, the effect of long-term warming on the activities of oxidases and hydrolases targeting C, nitrogen (N) and phosphorus (P) and their ratios is unclear, as well as whether and to what extend the response is modulated by long-term fertilization. A 9-year field experiment in the North China Plain, including an untreated control, warming, N fertilization, and combined (WN) treatment plots, compared the factorial effect of warming and fertilization. Long-term warming interacted with fertilization to stimulate the highest activities of C, N, and P hydrolases. Activities of C and P hydrolase increased from 8 to 69% by N fertilization, 9 to 53% by warming, and 28 to 130% by WN treatment compared to control, whereas the activities of oxidase increased from 4 to 16% in the WN soils. Both the warming and the WN treatments significantly increased the enzymatic C:N ratio from 0.06 to 0.16 and the vector length from 0.04 to 0.12 compared to the control soil, indicating higher energy and resource limitation for the soil microorganisms. Compared to WN, the warming induced similar ratio of oxidase to C hydrolase, showing a comparable ability of different microbial communities to utilize lignin substrates. The relationship analyses showed mineralization of organic N to mediate the decomposition of lignin and enzyme ratio in the long-term warming soil, while N and P hydrolases cooperatively benefited to induce more oxidase productions in the soil subject to both warming and N fertilization. We conclude that coupled resource limitations induced microbial acclimation to long-term warming in the agricultural soils experiencing high N fertilizer inputs.